2016
DOI: 10.1212/wnl.0000000000003322
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic cortical thinning in familial Alzheimer disease

Abstract: Objective:To identify a cortical signature pattern of cortical thinning in familial Alzheimer disease (FAD) and assess its utility in detecting and tracking presymptomatic neurodegeneration.Methods:We recruited 43 FAD mutation carriers—36 PSEN1, 7 APP (20 symptomatic, 23 presymptomatic)—and 42 healthy controls to a longitudinal clinical and MRI study. T1-weighted MRI scans were acquired at baseline in all participants; 55 individuals (33 mutation carriers; 22 controls) had multiple (mean 2.9) follow-up scans a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 31 publications
2
58
0
Order By: Relevance
“…Affected cognitive functions overlap with those in the current study, including tests of memory and executive function. These investigators also showed a linear correlation between lower flow and cortical thinning, a marker also associated with cognitive impairment [25,26]. This correlation was also demonstrated in patients with carotid disease [27].…”
Section: Discussion/conclusionmentioning
confidence: 68%
“…Affected cognitive functions overlap with those in the current study, including tests of memory and executive function. These investigators also showed a linear correlation between lower flow and cortical thinning, a marker also associated with cognitive impairment [25,26]. This correlation was also demonstrated in patients with carotid disease [27].…”
Section: Discussion/conclusionmentioning
confidence: 68%
“…On the other hand, lower 5‐HIAA levels correlated also with a large cluster of atrophy in the precuneus, which is a multimodal cortical hub integrating information from temporal, occipital, and parietal lobes . The precuneus is a very vulnerable region of the aging brain, as its atrophy and dysfunction has been associated with early phases of Alzheimer's disease . Thus, the association between GM atrophy of this specific area with lower 5‐HIAA/5‐HTP CSF levels might reflect the interaction of chronic serotonin depletion specifically present in PKU patients and the time‐dependent changes in the human brain.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the ROIs were chosen on the basis of being early sites of neuropathological change in AD. These included four regions that comprise the Mayo Clinic cortical signature of AD (entorhinal cortex, inferior temporal gyrus, middle temporal gyrus, and fusiform gyrus) (Jack et al, ; Schwarz et al, ), all of which have been implicated to undergo grey matter atrophy at a relatively early stage of AD (Braak and Braak, ; Dickerson et al, ; Jack et al, ; Petersen et al, ; Weston et al, ) and the precuneus, which has been reported to undergo more pronounced atrophy in YOAD patients (Ishii et al, ; Karas et al, ; Möller et al, ). To investigate if cortical NODDI metrics are potentially a more sensitive marker of AD pathology than cortical macrostructural metrics, the precentral gyrus (primary motor cortex) was included as a ROI.…”
Section: Methodsmentioning
confidence: 99%
“…To provide a mask for field map processing a total intracranial mask (Malone et al, 2015) generated from SPM12 (http://www.fil.ion.ucl.ac.uk/spm) segmentation was propagated from the T1 to diffusion volumes by a union of direct affine transformation and nonlinear transformation to provide maximal coverage before and after susceptibility correction. Structural T1 to diffusion b 5 0 and diffusion to field map magnitude registration was carried out using Niftyreg ( all of which have been implicated to undergo grey matter atrophy at a relatively early stage of AD (Braak and Braak, 1991;Dickerson et al, 2011;Jack et al, 2017;Petersen et al, 2016;Weston et al, 2016) and the precuneus, which has been reported to undergo more pronounced atrophy in YOAD patients (Ishii et al, 2005;Karas et al, 2007;M€ oller et al, 2013). To investigate if cortical NODDI metrics are potentially a more sensitive marker of AD pathology than cortical macrostructural metrics, the precentral gyrus (primary motor cortex) was included as a ROI.…”
Section: Diffusion-weighted Mri Processingmentioning
confidence: 99%